Implementasi Media Pembelajaran Al-Qur'an berbasis Permainan: Inovasi Ular Tangga Islami sebagai Stimulus Multi-Domain Anak - Endiana, Yeni; Fauziyah, Ni'matul (Fahima, 2025)
The Islamic Snakes and Ladders game is an innovative learning media designed to increase children's interest in learning the Qur'an through a fun learning approach. This game combines elements of entertainment and education by presenting visually engaging features such as the name of the surah, its meaning, the number of verses, its order, and the city where the surah was revealed. The aim of this research is to identify the Islamic Snakes and Ladders game as an interactive media in developing Qur’anic individuals among teenagers. The researcher will analyze in-depth how the Islamic Snakes and Ladders game serves as a medium for learning the Qur'an, its advantages and disadvantages, and which aspects are stimulated after playing this game. The research method used is descriptive qualitative. Data is collected through observation, interviews, and documentation. The research findings indicate that this game is effective in helping children memorize and understand the contents of the Qur'an, increasing learning motivation, and improving social and motor skills. The advantages of this game include its interactive design, flexibility, and cost-effectiveness. However, the game also has drawbacks, such as its long duration and limited material coverage. Therefore, the Islamic Snakes and Ladders game can be an alternative creative learning media that is relevant and enjoyable to support children's education, especially in Qur'anic learning. In its process, this game can stimulate children's affective, linguistic, cognitive, and psychomotor aspects.